2005
DOI: 10.1007/s10541-005-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability and Hemolytic Activity of Actinoporin RTX-SII from the Sea Anemone Radianthus macrodactylus

Abstract: The spatial organization of actinoporin RTX-SII from the sea anemone Radianthus macrodactylus on the level of tertiary and secondary structures was studied by UV and CD spectroscopy and intrinsic protein fluorescence. The specific and molar extinction coefficients of RTX-SII were determined. The percentages of canonical secondary structures of actinoporin were calculated. The tertiary structure of the polypeptide is well developed and its secondary structure is highly ordered and contains about 50% antiparalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…(45,46) It is well recognized that heat treatment (>65°C) for 30-60 min eliminates the cytotoxicity of RTX toxins. (47) However, we recently demonstrated that a brief heat treatment of the M. haemolytica LKT resulted in greater cytotoxicity, (48) which was accompanied by an irreversible change in secondary structure as determined by circular dichroism (CD) spectroscopy. Varied biophysical approaches have identified other proteins (e.g.…”
Section: Original Articlementioning
confidence: 99%
“…(45,46) It is well recognized that heat treatment (>65°C) for 30-60 min eliminates the cytotoxicity of RTX toxins. (47) However, we recently demonstrated that a brief heat treatment of the M. haemolytica LKT resulted in greater cytotoxicity, (48) which was accompanied by an irreversible change in secondary structure as determined by circular dichroism (CD) spectroscopy. Varied biophysical approaches have identified other proteins (e.g.…”
Section: Original Articlementioning
confidence: 99%
“…It has been shown previously that exposure of LKT to high temperature (90–100 °C) for 30 minutes or more, largely eliminates cytotoxic activity for bovine leukocytes [13]. However, other studies showed that exposure of some bacterial toxins to high temperature has varying bio-physical effects on those toxins [22].…”
Section: Introductionmentioning
confidence: 99%